Evaluation of the effects of the COVID‐19 pandemic on dentistry - Osman Evren Çelik; İbrahim Hüseyin Cansever (Wiley, 2021)
Abstract Objectives The aim of this study is to evaluate dentists' working conditions and the policies implemented for dentistry during the COVID‐19 pandemic. In addition, effects of working in private practice or governmental practice in terms of pandemic are also evaluated in the manuscript. Methods A questionnaire was prepared to elicit dentists' working conditions during the pandemic and analyze and evaluate the policies implemented for dentistry. The questionnaires were sent to the dentists registered in the Turkish Dental Association (TDA) via e‐mail, and collected between September 30, 2020, and October 20, 2020. Descriptive statistical methods, validity and reliability analysis, and regression analysis were applied for data analysis. Results Seven hundred thirty‐four dentists registered in the Turkish Dental Association took part in the study. 47% of respondents examined five or fewer patients per day during the pandemic. Dentists working in private practice examine more patients per day during the pandemic. 80.8% of the respondents experienced anxiety while examining patients during the pandemic. While the dentist's anxiety level increased with increasing the number of patients examined per day (β: 0.399), it decreased with increasing the dentist's age (β: −0.065). Respondents were not satisfied with the pandemic's management, with the decisions taken regarding dentistry, and with the supports provided to the dentists. 85.8% of the respondents were concerned about their professional future, which is higher among dentists who work in governmental practice (p < 0.05, ANOVA). Conclusions Increasing dentists' representation in the management of the pandemic and the future policy‐making process, taking steps for the future by creating planning processes will eliminate the uncertainties and dissatisfaction and ensure to be ready for new pandemics.